African American preachers and politics : the Careys of Chicago - Dickerson, Dennis C., 1949- (Margaret Walker Alexander series in African American studies., 2010)
During most of the twentieth century, Archibald J. Carey, Sr. (1868-1931) and Archibald J. Carey, Jr. (1908-1981), father and son, exemplified a blend of ministry and politics that many African American religious leaders pursued. Their sacred and secular concerns merged in efforts to improve the spiritual and material well-being of their congregations. But as political alliances became necessary, both wrestled with moral consequences and varied outcomes. Both were ministers to Chicago's largest African Methodist Episcopal Church congregations- the senior Carey as a bishop, and the junior Carey.